Physical methods of YSZ film application on solid oxide fuel cell electrolyte - Opakhay, S. (Recent Contributions to Physics, 2020)
Today high effective and sensitive physical methods are used to deposit thin and durable YSZ films (zirconium oxide stabilized by yttrium) for a solid oxide fuel cells electrolyte. The review article is intended to analyze the advantages and disadvantages of perspective physical methods used in the papers of various authors, such as reactive magnetron and plasma sputtering, pulsed laser deposition. One of the main advantages of the pulsed laser deposition method is the choice of the background gas and the ambient pressure during the emission of the ultraviolet camera and the evaporation energy, however, the penetration of microporous particles and target particles on the substrate surface leads to structural changes caused by deformation of the film, as well as a change in the morphology of the film surface YSZ. In this paper, the advantages and disadvantages of the remaining methods are discussed in detail by comparing the articles of the authors. In particular, from the above methods, special attention is paid to the features of the reactive magnetron sputtering method, and it is shown that this method is the most effective, sensitive, expressive method for future use.